Observational research social network: interaction and security - Lopes, Rui Pedro (2014)
Quality in education depend heavily on the teachers’ professional development, as a mean for pedagogical methodologies and practice improvement. In this sense, learning is enhanced by sharing and working in a community of practice, a learning organization that generate knowledge and allow members to innovate. In this context, children observation is fundamental, allowing a sound basis for reflection and action around learning experiences and teaching environments. Specific guidelines and programs, such as the EEL/DQP, can help reducing the inherent subjectivity, providing a common base for teachers and the preschool education community. In this paper we propose an online, web based community to improve the observation process as well as the communication between researchers. The social relations are identified and the security issues are discussed.